Very low calorie ketogenic diet combined with physical interval training for preserving muscle mass during weight loss in sarcopenic obesity: A pilot study - Camajani, Elisabetta; Feraco, Alessandra; Proietti, Stefania; Basciani, Sabrina; Barrea, Luigi; Armani, Andrea; Lombardo, Mauro; Gnessi, Lucio; Caprio, Massimiliano (Frontiers in Nutrition, 2022)
The prevalence of sarcopenic obesity (SO) is increasing worldwide, posing important challenges to public health and national health care system. In subjects with SO, it is essential to reduce body weight preserving lean mass. Lifestyle modification with adequate nutrition and proper physical activity is essential to counteract SO progression. Very Low Calorie Ketogenic Diet (VLCKD) has been indicated for the treatment of SO. To date, the effects of physical training during VLCKD have not been investigated. This pilot study aims to determine the efficacy of VLCKD combined with interval training, compared to a VLCKD alone, on weight loss, improvement of body composition and physical performance in patient with SO. Twenty-four patients with SO, aged between 50 and 70 years, who met the inclusion criteria, accepted to adhere to a VLCKD were enrolled in the study. Twelve patients followed a VLCKD protocol (VLCKD group) and twelve patients followed a VLCKD protocol combined with interval training (IT), twice per week (VLCKD+IT group). Data were collected at baseline and after six-week of treatment. Anthropometric indexes, body composition analysis by Bioelectrical Impedance Analysis, muscle strength and physical performance analysis were assessed at baseline and at the end. At the end of the study, Body Mass Index, body weight, waist circumference and hip circumference were significantly reduced both in the VLCKD group and in the VLCKD+IT group. Interestingly, a significant improvement of muscle strength and physical performance was observed in both groups. A multiple comparison of delta variations in all parameters between groups was performed. No differences were observed for the majority of anthropometric and biochemical parameters, with the exception of fat free mass (FFM) and fat mass (FM): notably, subjects who followed a VLCKD combined with IT preserved FFM (p <0.001) and reduced FM (p = 0.001) to a greater extent than what observed in VLCKD group. Moreover, HDL plasma levels were significantly increased in the VLCKD+IT group compared to the VLCKD group. This pilot study confirms that VLCKD is effective in terms of body weight reduction, particularly FM; moreover, the combination of VLCKD and interval training determined a better preservation of FFM.